Manajemen Sarkopenia - Yunita, Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to improve understanding of sarcopenia and develop effective strategies to prevent, diagnose, treat, or manage sarcopenia. The method used is descriptive-analytical in the form of a case study. The study results indicate that the management of sarcopenia uses two main principles, namely physical exercise intervention and nutritional intervention. Physical exercise 3-4 times a week for 3 months will show significant muscle mass and strength changes in sarcopenia patients. Providing protein in the form of leucine-enriched protein or whey is very effective in increasing muscle mass. Increasing protein intake by 1.2 grams/kg BW/day is recommended in patients with sarcopenia. In conclusion, sarcopenia often occurs in the elderly, which causes mobility disorders. Sarcopenia management that can be done today is a combination of physical activity, especially resistance training, and fulfillment of nutritional adequacy, including protein, vitamins, and minerals. Keywords: Management, Aging, Sarcopenia